Legal Counseling to Teachers and Students regarding Educational Actions towards Students at SMP Muhammadiyah 2 Malang - Kurniawan, Wahyudi; Hartini, Rahayu (Universitas Muhammadiyah Malang, 2024)
The problem of teachers and education personnel at SMP Muhammadiyah 2 Malang is the ignorance of parents or guardians, including students, about the actions of educating teachers at school. Considering that this educational action is a process of educating and disciplining students, knowledge about this is needed, considering that legal proceedings often occur against teachers and staff who are deemed to have committed violence against students. So the community service feels the need to contribute to help provide appropriate counseling or education needed by society. So the role of a teacher in educating, teaching, guiding, directing, training, assessing, and evaluating so that educators are given the authority to rewards and punishment to students is not violence. Abstrak Permasalahan yang dihadapi oleh Guru dan Tenaga Kependidikan di SMP Muhammadiyah 2 Malang adalah ketidaktahuan orang tua atau wali murid termasuk siswa tentang tindakan mendidik guru di sekolah. Mengingat bahwa tindakan mendidik ini, merupakan proses mendidik dan mendisiplinkan siswa maka pengetahuan tentang hal tersebut sangat dibutuhkan, mengingat sering terjadi proses hukum kepada guru maupun tenaga kependidikan yang dianggap melakukan kekerasan kepada siswa.. Maka pengabdi merasa perlu untuk berkontribusi membantu memberikan penyuluhan atau edukasi yang dibutuhkan oleh masyarakat. Maka peran seorang guru dalam mendidik, mengajar, membimbing, mengarahkan, melatih, menilai, dan mengevaluasi peserta didik, sehingga pendidik diberi kewenangan untuk memberikan penghargaan dan punishment kepada siswa bukanlah sebuah kekerasan.